Evaluación Financiera a la Fundación de Investigación y Capacitación para el Desarrollo Integral Panel de la Ciudad de Loja, período 2014 - Valle Espinosa, Betty Alexandra (2016)
This thesis was applied to the Foundation for Research and Training Panel integral development of the city of Loja , dedicated to providing consulting services , training, productive enterprises the southern region and the whole country ; In order to implement the Financial Assessment to the Foundation research and training for the integral development Panel of the city of Loja , period 2014 to complement you have specific objectives as they are to assess the economic and financial position 2014 of the Panel Foundation the city of Loja to contribute to making management decisions , apply financial indicators most commonly used to provide information for the financial evaluation and report where alternative solution proposals establish their managers for sound decision –making The methodology used for the development of this thesis began with the gathering of information , continued with the implementation of indicators of liquidity, profitability , activity and indebtedness that after their analysis allowed to know the state in which the foundation is establishing the different problems faced in the reporting period. In the results, the Vertical Analysis of Financial Statements of the foundation is done , financial and non-financial indicators are applied and the respective interpretation is made , also the Dupont System was applied in the discussion is